A Prospective Observational Study on the Management of Difficult Airway in Neonates with Congenital Anomalies in a Tertiary Care Centre - Ganne , Neelima; C Patil, Manjunath; A Kamat , Chaitanya (Journal of Neonatal Surgery, 2025)
Background: Airway management in neonates with congenital anomalies is challenging due to anatomical abnormalities and limited physiological reserve. “Difficult airway situations can lead to significant morbidity and mortality if not managed appropriately. Aim: To study the management of difficult airway in neonates with congenital anomalies. Objective: To evaluate various airway management techniques and their outcomes in neonates presenting with difficult airway. Methods: This prospective observational study was conducted in a tertiary care centre including 30 neonates with congenital anomalies presenting with difficult airway. Data on demographic profile, type of anomaly, airway management techniques, use of adjuncts, and outcomes were collected. Statistical analysis was performed, and associations were assessed using appropriate tests with significance set at p < 0.05. Results: Craniofacial anomalies were the most common cause of difficult airway. Difficult mask ventilation and ≥3 intubation attempts were significantly associated with adverse outcomes (p < 0.05). Use of adjuncts such as videolaryngoscopy and laryngeal mask airway significantly improved success rates (p < 0.05). Overall airway success rate was 90%, with complications including desaturation (50%) and bradycardia (30%). Conclusion: Difficult airway in neonates with congenital anomalies requires a structured approach with early use of adjuncts and limitation of repeated attempts”. Adoption of standardized protocols and simulation-based training can improve outcomes and reduce complications.